Imagens no ensino de História: Cândido Portinari em livros didáticos - Daniel Fernando do Carmo (2021)
This dissertation aims to analyze the ways in which images are treated in History textbooks in Brazilian basic education. Assuming that images are potential sources for studies in the field of History, endowed with their own languages that demand specific methodologies for their analysis and understanding, it is intended to verify the path of understanding the value of these sources and the ways in which they were worked in a sample of sixteen History textbooks between 1998 and 2020. Special attention is given to pictorial images from the Brazilian visual arts and the historical subject and artist Cândido Portinari, in view of his notorious reading and representation of Brazilian identities that contributed to the formation of consciences and historical narratives about Brazil in the 20th century. In its final part, the text develops a look at didactic sequences in the context of contemporary education, and presents proposals for didactic sequences for the teaching-learning of History based on pictorial productions by Cândido Portinari.